Accuracy of sport action cameras for 3D underwater motion analysis - Bernardina, G. R. D.; Goncalves Silva, R.; Cerveri, P.; de Barros, R. M. L.; Silvatti, A. P. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to evaluate the accuracy of sport action cameras for 3D underwater motion analysis. Two cameras (GoPro) were fixed in the swimming pool. The image resolution was set to 1920 x 1080, the view angle was set to 127o and the frame rate was 60 Hz. A Wi-Fi remote was used to start the cameras. A wand calibration method based on radial distortion model was used to calibrate the cameras. The accuracy was evaluated in eight trials of dynamic rigid bar tests (working volume 4?1?1.5m3). The results revealed mean absolute error ranging from 1.23 mm to 1.93 mm. These values of accuracy for underwater analysis can be considered acceptable for the majority of 3D underwater motion analyses, in particular for swimming biomechanics.